The physical, chemical and mineralogical characteristics of Jambu Soil Series - Abd Shukor, Nurfadlun Aini (2015)
BRIS soil originates from sand from the sea that accumulated from the erosion of layers of steep cliffs by the sea during monsoon seasons and has coarse sand component. This study focused on the mineralogical content, physical and chemical properties also light and heavy mineral of Jambu Series in BRIS soil. The study shows information about the potential of the soil fertility. BRIS soil has a reputation of being a problematic soil, which are extremely leaching, low cation capacity (CEC) and low exchangeable bases that does not support plant growth. The objectives of the study were to determine the physical, chemical and mineralogical characteristics of the Jambu Soil Series. Data collected were subjected to the Analysis of Variance (ANOVA) and Least Significant Difference (LSD) test. Result of the physical analysis of the soil was recorded with low CEC and low exchangeable capacity. The texture was dominated by sand content (exceeding 90%). Based on the data that was analyzed, light mineral showed a high percentage (> 90%) compared to heavy minerals. The mineralogical data obtained from the XRD analysis shows the dominance of quartz. BRIS soil was characterized for being physically, chemically and mineralogically unfertile for agriculture.